The Never Girls. Volume 3, books 7-9 - Thorpe, Kiki (Thorpe, Kiki. Never girls., 2017)
In three stories, Mia makes treats for a bake sale; Kate and her friends cannot wait to meet Peter Pan, although he may cause trouble; and Gabby goes to her first day of school.